Karakter Visual Keindonesiaan dalam Iklan Cetak di Indonesia - Didit Widiatmoko Suwardikun (ITB Journal Publisher, LPPM ITB, 2008)
Many have tried to explore the unified identity character of an Indonesian, arousing certain tribal cultures to visually represent